Design, synthesis and characterization of enzyme-analogue-built polymer catalysts as artificial hydrolases - Divya Mathew; Benny Thomas; Karakkattu Subrahmanian Devaky (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
In this review, the concept and various strategies in molecular imprinting is discussed briefly. How the concept of transition state analogue can be used to design a template to prepare catalytic imprinted polymers is described in detail. The use of the “bait and switch” approach and alternative covalent template strategies show how functional groups which assist in the catalytic properties can be assembled within the imprint. Thus, there are so many reports on P catalyzed reactions. Owing to their advantageous properties over natural biological recognition agents, molecularly imprinted polymers (MIPs) therefore offer great potential for various applications.